Crimean Tatars Documents in the archive of Abdureshid Mediev - Il’ya Zaytsev (Крымское историческое обозрение)
The article represents documents in the Crimean Tatar and Turkish languages, preserved among the papers of the Crimean Tatar public activist, deputy of the Second State Duma Abdureshid Mediev (1880–1912). These documents are now kept in the State Museum of Taurida in Simferopol. The archive consists of letters to A. Mediev from numerous correspondents (A.S. Aivazov; Ali A Tarpi; Muhammad Tukayev; Muhammad-bek Khadzhetlashe; Ahmed Saib Kaplan; Hassan Nuri, etc.). Among A. Mediev’s papers there are documents of other persons in Turkish and Crimean Tatar: by A. Aivazov “Reform of Islamism”; the rules for the election of the Mufti and Qadiasker by the Taurida Mohammedan Spiritual Board etc. The originals of several legal documents from the era of the Crimean Khanate are of great interest.